1991
DOI: 10.1111/j.1365-2559.1991.tb00870.x
|View full text |Cite
|
Sign up to set email alerts
|

Monocytoid B‐cell lymphoma: morphological variants and relationship to low‐grade B‐cell lymphoma of the mucosa‐associated lymphoid tissue

Abstract: Twenty-eight cases of monocytoid B-cell lymphoma of lymph nodes and 16 lymph node metastases of primary gastric lymphomas, mostly low-grade B-cell lymphomas of mucosa-associated lymphoid tissue (MALT) type were investigated morphologically and immunohistochemically. Both groups showed the same morphological and immunohistochemical features: diagnostically important sites of infiltration were the sinuses and the marginal zones. The tumour cells were either medium-sized or small. The cytoplasm stained grey with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(38 citation statements)
references
References 31 publications
1
37
0
Order By: Relevance
“…It has been suggested that a substantial proportion, if not all of the cases may represent the nodal manifestation of a primary extranodal lymphoma. [32][33][34] In addition, a primary nodal counterpart of splenic MZBL characterized by absent or attenuated mantle cuffs and negativity of the tumor cells for IgD was recently described. 12 In our cases, after careful re-evaluation, there was no clinical or histological evidence for a primary extranodal origin.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that a substantial proportion, if not all of the cases may represent the nodal manifestation of a primary extranodal lymphoma. [32][33][34] In addition, a primary nodal counterpart of splenic MZBL characterized by absent or attenuated mantle cuffs and negativity of the tumor cells for IgD was recently described. 12 In our cases, after careful re-evaluation, there was no clinical or histological evidence for a primary extranodal origin.…”
Section: Discussionmentioning
confidence: 99%
“…lymphoma of the mucosa associated lymphoid tissue) and NMZL. 4,5 In the REAL classification of 1994, and in the 2001 WHO classification, NMZL was adopted as a provisional entity. 6,7 In the current 2008 WHO classification, NMZL has become a definitive entity and a pediatric variant has been included.…”
Section: Classification Of Nmzlmentioning
confidence: 99%
“…7 Lymphomas comprised of MBLs develop most commonly in adult patients with a history of autoimmune disease such as Sjogren's syndrome. [8][9][10] It has been suggested that the background of immune dysfunction may provide a predisposing substrate for subsequent development of lymphoma. MBCLs and low-grade lymphomas of mucosa-associated lymphoid tissue (MALT) share several common histologic, immunophenotypic, and clinical features, suggesting they are related entities.…”
mentioning
confidence: 99%